Pengaruh Pendidikan Karakter Dan Disiplin Belajar Terhadap Prestasi Belajar IPS Siswa Kelas VIII SMP Negeri 6 Pematang Siantar Tahun Ajaran 2023/2024 - Michael Putra Tama Tambun; Tumpal Manahara Siahaan; Herlina Hotmadinar Sianipar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the effect of character education and learning discipline on the social studies learning achievement of class VIII IPS students at SMP Negeri 6 Pematang Siantar for the 2023/2024 academic year. This research was carried out at SMP Negeri 6 Pematang Siantar for the 2023/2024 academic year in October 2023 with a population of 171 people consisting of 5 classes and a sample of 120 people using a simple random sampling technique. Data collection techniques in this research were documentation and questionnaires. The results of simple linear regression test calculations on student learning achievement were obtained Y = 61.07 + 0.45 X1 The results of simple linear regression test calculations on student learning achievement were obtained Y = 52.33 + 0.57 X2 Results of the significance test of the contribution between variables on the influence of character education on student learning achievement X1 (X1) obtained 37.84. The results of the significance test of the contribution between variables on the influence of learning discipline on student learning achievement (X2) were obtained as 2753.1217